2023
DOI: 10.3390/ejihpe13020029
|View full text |Cite
|
Sign up to set email alerts
|

Zarit Caregiver Burden Interview: Psychometric Properties in Family Caregivers of People with Intellectual Disabilities

Abstract: Caregivers of people with intellectual disabilities may feel overburdened in their work and experience negative psychological consequences. The purpose of this instrumental study was to determine the evidence of internal structure and reliability of the Zarit Caregiver Burden Interview scale. A total of 398 family caregivers, including women and men, participated (M = 47.33, SD = 10.44). The structure of the scale was evaluated by factor analysis and the McDonald Omega coefficient was used to estimate reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Two coders were used to ensure rigorous coding process and a third reviewer was consulted in any case of disagreement. The themes were then categorized in domains and subdomains as they related to factors that highlighted additional burdens not captured by the Zarit Caregiver Burden Questionnaire 22,23 , such as areas of bene t and factors that enhanced their quality of life as experienced in caring for their child.…”
Section: Discussionmentioning
confidence: 99%
“…Two coders were used to ensure rigorous coding process and a third reviewer was consulted in any case of disagreement. The themes were then categorized in domains and subdomains as they related to factors that highlighted additional burdens not captured by the Zarit Caregiver Burden Questionnaire 22,23 , such as areas of bene t and factors that enhanced their quality of life as experienced in caring for their child.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The ZBI-22 has also been validated among informal caregivers of patients with schizophrenia and found to be an appropriate tool by experts. 31 , 32 , 33 According to other investigators, the ZBI-22 is the gold standard for assessing family caregiver burden in patients with schizophrenia. 34 …”
Section: Methodsmentioning
confidence: 99%
“…Categorical variables were expressed as frequency and percentages (Table 1, Table 2, and Table 3). The prevalence of the four categories of severity of caregiver burden (none to low [0-20]; mild to moderate [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]; moderate to severe [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]; severe [61-88]) was also expressed as frequency and percentage with its 95% confidence interval (CI). The normality of the continuous variables was assessed with multiple measures including the skewness-kurtosis test.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
“…Scores range from 0 (indicating no burden) to 88 (signifying very high burden). 17 In a previous study the ZBI has been demonstrated to be a good predictor of the impact of PWS on many aspects of the caregiver quality of life and thus could be considered an efficient instrument to capture the global impact of PWS on the caregiver. 18 The telephonic interview, lasting around 15 minutes, ensured anonymity in data collection.…”
Section: Methodsmentioning
confidence: 99%